دراسة تحليلية اقتصادية لتربية دجاج اللحم (الفروج ) في محافظة اللاذقية - درويش, نضال (Latakia University Journal -Biological Sciences Series, 2013)
نتيجة لأهمية مسألة الأمن الغذائي في الدول العربية بشكل عام وسورية بشكل خاص ، فقد أكدت السياسة الزراعية في سوريا على استثمار كافة الطاقات والموارد الزراعية لإنتاج وتوفير الغذاء ، ومن هنا جاء التفكير في إنتاج لحوم الدواجن في الفروع التجارية الحديثة التي لا تتأثر كثيراً بالعوامل الطبيعية والظروف المناخية, والتي تتميز بانخفاض أسعارها وسرعة دوران رأس المال في إنتاجها, ولأنها من أكثر أنواع اللحوم احتواءً على البروتين الحيواني . وقد هدف هذا البحث إلى تحقيق الأهداف التالية : 1ـ تحليل التكاليف الإنتاجية لإنتاج دجاج اللحم (الفروج) في محافظة اللاذقية . 2 ـ التقويم الاقتصادي لإنتاج دجاج اللحم (الفروج) في محافظة اللاذقية . ونتيجة الدراسة تبين أن أهم النتائج التي توصل إليها البحث هي : 1 ـ بلغ صافي الربح السنوي المحقق في المزرعة ( الدونم الواحد ) /1059662.4 / ل . س 2 ـ بلغت الكفاءة الإنتاجية لتربية دجاج اللحم (الفروج) في محافظة اللاذقية 1.36 3 ـ بلغت الكفاءة الاقتصادية الإجمالية لتربية دجاج اللحم في محافظة اللاذقية 1.53 Due to the importance of food security in the Arab Countries in general and in Syria in particular, the agricultural policy in Syria has emphasized on exploiting all the energies and agricultural resources for the production and provision of food. Hence came the thinking in producing poultry meat in the modern commercial sectors which are not much affected by natural factors and climatic conditions. They are characterized by their low prices and the fast capital turnover when producing them. They are one of the most types of meat that highly contain animal protein. This research aims to achieve the following objectives: 1- Analyzing production costs of table chicken in Lattakia Governorate. 2- Economic assessment for the production of table chicken in Lattakia Governorate. The study conclusion shows the most important results reached by the research, and they are: 1- The annual net profit achieved in the farm (per dunum) amounted to /1059662.4/ Syrian Pounds. 2- The production efficiency for table chicken breeding in Lattakia Governorate amounted to /1.36/. 3- The total economic efficiency for table chicken breeding in Lattakia Governorate amounted to /1.53/.